Glucocerebrosidase Defects as a Major Risk Factor for Parkinson’s Disease - Avenali, Micol; Blandini, Fabio; Cerri, Silvia (Frontiers in Aging Neuroscience, 2020)
Heterozygous mutations of the GBA1 gene, encoding for lysosomal enzyme glucocerebrosidase (GCase), occur in a considerable percentage of all patients with sporadic Parkinson’s disease (PD), varying between 8% and 12% across the world. Genome wide association studies have confirmed the strong correlation between PD and GBA1 mutations, pointing to this element as a major risk factor for PD, possibly the most important one after age. The pathobiological mechanisms underlying the link between a defective function of GCase and the development of PD are still unknown and are currently the focus of intense investigation in the community of pre-clinical and clinical researchers in the PD field. A major controversy regards the fact that, despite the unequivocal correlation between the presence of GBA1 mutations and the risk of developing PD, only a minority of asymptomatic carriers with GBA1 mutations convert to PD in their lifetime. GBA1 mutations reduce the enzymatic function of GCase, impairing lysosomal efficiency and the cellular ability to dispose of pathological alpha-synuclein. Changes in the cellular lipidic content resulting from the accumulation of glycosphingolipids, triggered by lysosomal dysfunction, may contribute to the pathological modification of alpha-synuclein, due to its ability to interact with cell membrane lipids. Mutant GCase can impair mitochondrial function and cause endoplasmic reticulum stress, thereby impacting on cellular energy production and proteostasis. Importantly, reduced GCase activity is associated with clear activation of microglia, a major mediator of neuroinflammatory response within the brain parenchyma, which points to neuroinflammation as a major consequence of GCase dysfunction. In this present review article, we summarize the current knowledge on the role of GBA1 mutations in PD development and their phenotypic correlations. We also discuss the potential role of the GCase pathway in the search for PD biomarkers that may enable the development of disease modifying therapies. Answering these questions will aid clinicians in offering more appropriate counseling to the patients and their caregivers and provide future directions for PD preclinical research.